#### Answer

The simplified value is $ -7 $.

#### Work Step by Step

$ =\frac{9[4-(1+6)]-(3-9)^2}{5+\frac{12}{5-\frac{6}{2+1}}} $
Start from the lowest term of the denominator.
$ =\frac{9[4-(1+6)]-(3-9)^2}{5+\frac{12}{5-\frac{6}{3}}} $
$ =\frac{9[4-(1+6)]-(3-9)^2}{5+\frac{12}{5-2}} $
$ =\frac{9[4-(1+6)]-(3-9)^2}{5+\frac{12}{3}} $
$ =\frac{9[4-(1+6)]-(3-9)^2}{5+4} $
$ =\frac{9[4-(1+6)]-(3-9)^2}{9} $
Now solve the numrator by using BODMAS rule.
$ =\frac{9[4-7]-(3-9)^2}{9} $
$ =\frac{9[-3]-(-6)^2}{9} $
$ =\frac{-27-36}{9} $
$ =\frac{-63}{9} $
$ =-7 $